Contracts for agents with biased beliefs: Some theory and an experiment - Anja Sautmann (Brown University, Department of Economics, 2011)
This paper experimentally tests the predictions of a principal-agent model in which the agent has biased beliefs about his ability. Overconfident workers are found to earn lower wages than underconfident ones because they overestimate their expected payoff, and principals adjust their offers accordingly. Moreover, the profit-maximizing contract distorts effort by varying incentives according to self-confidence, although only the most successful principals use this strategy. These findings have implications for the labor market; in particular, self-confidence is often correlated with gender, implying that principals would prefer to hire men over women simply because they are more overconfident.
Keywords: 330